The Relationship Between Resilience and Well-Being on Suicidal Ideation - Purba, Novia Sri Parindu; Jatmika, Devi (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2024)
Suicidal ideation refers to thoughts about planning and behaviors that can lead to actual and fatal suicide attempts. This research aims to examine whether there is a relationship between resilience and well-being and suicidal ideation. The study is a quantitative correlational study conducted among adolescents in Jakarta. The participants of this study numbered 139, obtained through incidental sampling techniques. The measurement tools used in this study are the Brief Resilience Scale, the Satisfaction with Life Scale (SWLS), and the Indonesian version of the Suicide Ideation Scale (R-SIS). Correlation analysis results show that resilience and well-being are jointly related to suicidal intention (p0.01). The study found a moderate relationship between resilience and subjective well-being simultaneously with suicidal ideation. The simultaneous contribution of these two variables to suicidal ideation is 19.6% (R = 0.442a, R² = 0.196, p = 0.000).